Ідея Соборності й українське державотворення (1918–1919 рр.) - Гай-Нижник, П. (Краєзнавство, 2019)
Досліджуються соборницько-державницькі прагнення українців Закарпаття, Буковини, Наддністрянської (Західної) та Наддніпрянської (Великої) України до об'єднання в єдиній самостійній
Українській державі у 1918–1919 рр. Висвітлюються передумови і перебіг укладання державної Злуки між ЗУНР та УНР. The author investigates the co-state-state aspirations of the Ukrainians of Transcarpathia, Bukovyna, the
Dniester- (Western) and Dnieper- (Great) Ukraine to unite in a single self-dependent Ukrainian state in 1918–
1919. The complex processes of national self-determination of various branches of the Ukrainian people and
the confrontation to its realization in the national state on the part of Austria, Hungary, Poland, Romania,
Czechoslovakia, etc. The Revolution of 1918 in Austria-Hungary strengthened the hopes of the Ukrainians of
Transnistria for the right to self-determination, and the fact of the existence of statehood in the Great Ukraine
gave them confidence in the inevitability of uniting the nation in the single Ukrainian Cossack Independent
State. The historical right of the Ukrainian people to a single Ukrainian state is stipulated. The preconditions
and the course of concluding the state unity between the WUPR and the UPR are highlighted.
However, the unification of the UNR and the ZUUR in one state in a number of circumstances was not
then brought to a logical conclusion. The legal and valid Act of Unification on the fact did not mean the real
merger of two entities of the agreement into a single state structure. It did not become the Cathedral of the
UPR after the unification of either a unitary state education, or a federal one. The UNR has retained its own
legislative and executive bodies with clearly defined scope and directions of their powers. The authorities of
the UNR Directory continued to be confined to the east of the Zbruch River. Each of the state formations
continued to dispose of its own troops, whose actions, in truth, were co-ordinated in a certain way by both
commanders and governments. In addition, de jure final decision on this merger was to be adopted by the
All-Ukrainian Constituent Assembly. Consequently, these two national Ukrainian formations (the UNR and
the UPR) were, rather, a confederative state association, which was caused both by objective and subjective reasons.